2020
DOI: 10.1155/2020/8653472
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Water Management towards Soil Moisture Preservation on Soybeans

Abstract: In this study, factorial randomized experiments were conducted in a controlled greenhouse environment to investigate an efficient and effective component of water management technology in increasing soybean yield. The soybeans were planted in polybags with 6 kg of Alfisol soil media and fertilizer. The bags were perforated with 16 holes at approximately 1 to 2 cm from the base and put into a water container. The container was immersed in water levels of 5 cm and 10 cm. The application of these immersions was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
2
4
0
Order By: Relevance
“…The longest root length was shown by the treatment of water when in full flowering, where this treatment showed that the soil was deprived of water due to water supply at once and only once so that the roots would extend themselves (root interception) to find further space to get water, this is in line with the study [18] which found that soybean plants that were stressed by water tended to extend themselves compared to plants that received normal irrigation.…”
Section: Resultssupporting
confidence: 81%
“…The longest root length was shown by the treatment of water when in full flowering, where this treatment showed that the soil was deprived of water due to water supply at once and only once so that the roots would extend themselves (root interception) to find further space to get water, this is in line with the study [18] which found that soybean plants that were stressed by water tended to extend themselves compared to plants that received normal irrigation.…”
Section: Resultssupporting
confidence: 81%
“…This is because almost every phase of plant growth and development is available enough water so that production is higher. This is in line with research by Aminah et al (2020) who found that continuous immersion with a water level of 5 cm increased soybean seed yield (seed weight) by 19.23% compared to field capacity. because this was supported by an increase in harvest components such as the number of pods and the number of seeds planted by 31.1% and 37.59% compared to field capacity, respectively.…”
Section: Production Parameterssupporting
confidence: 92%
“…Of the two photosynthetic pigments classes carotenoids show multifarious roles in tolerance to water deficit including light harvesting and protection from oxidative damage caused by soil water deficit (Kapoor et al, 2020). Aminah et al (2020) reported that keep a water surface at five centimeters increases the weight of soybean seed by 19.23%. The increase of harvest components in the number of pods and the number of seeds/crop by 31.1 % and 37.59% compared to field capacity.…”
Section: Resultsmentioning
confidence: 99%